2018
DOI: 10.1021/jacs.8b09063
|View full text |Cite
|
Sign up to set email alerts
|

Probing Hydrogen Atom Transfer at a Phosphorus(V) Oxide Bond Using a “Bulky Hydrogen Atom” Surrogate: Analogies to PCET

Abstract: Recent computational studies suggest that the phosphate support in the commercial vanadium phosphate oxide (VPO) catalyst may play a critical role in initiating butane C–H bond activation through a mechanism termed reduction-coupled oxo activation (ROA) similar to proton-coupled electron transfer (PCET); however, no experimental evidence exists to support this mechanism. Herein, we present molecular model compounds, (Ph2N)3VN–P­(O)­Ar2 (Ar = C6F5 (2a), Ph (2b)), which are reactive to both weak H atom donors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 59 publications
3
26
0
Order By: Relevance
“…However, because it has been shown that bis‐silyation of O 2 with variants of this silylating reagent occurs stepwise, it is premature to generalize about mechanisms of reductive silylation. In the end, different substrates may proceed by different mechanisms, as shown recently …”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…However, because it has been shown that bis‐silyation of O 2 with variants of this silylating reagent occurs stepwise, it is premature to generalize about mechanisms of reductive silylation. In the end, different substrates may proceed by different mechanisms, as shown recently …”
Section: Resultsmentioning
confidence: 83%
“…In the end, different substrates mayp roceed by different mechanisms, as shownr ecently. [19] Broader application can be envisioned. This silylation reagent has potential fors toichiometricu se in derivatizationo f N 2 -derived nitride complexes, and in am echanistically simpler manner than use of KC 8 with Me 3 SiCl.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, elsewhere in the literature hydrogen-transfer was reported on a P=O moiety in a molecular complex. [11] Over the P=O containing complex, hydrogen-transfer was observed and studied mecha-nistically, providing first experimental evidence of reductioncoupled oxo activation (ROA) mechanism, which is similar to the proton-coupled electron transfer (PCET) mechanism. [11] Based on results in the present study and the findings from the literature, it is likely that the P=O surface sites are the active sites for the surface-mediated hydrogen-transfer reaction in SPCs.…”
Section: Effect Of Surface Brønsted Aciditymentioning
confidence: 98%
“…[10] Little direct evidence corroborating an active role of surface phosphate sites in the hydrogen-transfer reaction can be found in the literature. In one instance, hydrogen-transfer was studied mechanistically on P=O containing moiety in a molecular complex [11] providing the first experimental evidence of reduction-coupled oxo activation (ROA) mechanism, which is similar to the proton-coupled electron transfer (PCET) mechanism. [11] Elsewhere, an IR study of SiO 2 -supported phosphate catalysts reported the formation of new surface À OH sites upon NH 3 adsorption on the catalyst but did not expand upon the observed phenomenon and the underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation